2017
DOI: 10.1007/s00256-017-2584-y
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided percutaneous screw fixation plus cementoplasty in the treatment of painful bone metastases with fractures or a high risk of pathological fracture

Abstract: Our results suggest that PSFPC might be a safe and effective procedure that allows the stabilization of the fracture and the prevention of pathological fractures with significant pain relief and good recovery of walking ability, although further studies are required to confirm this preliminary experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 15 publications
0
38
0
Order By: Relevance
“…17 Similar results have been confirmed by two additional studies. 20,27 Pusceddu et al have demonstrated that the mean VAS score decreased from 7.1 before treatment to 1.6 at 1 month and to 1.4/10 at 6 months, demonstrating a long-term effect. 20 Similarly, a double-center retrospective analysis of percutaneous FICS demonstrated 87.1% rate of pain improvement in a series of cancer patients that included 25 pelvic locations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…17 Similar results have been confirmed by two additional studies. 20,27 Pusceddu et al have demonstrated that the mean VAS score decreased from 7.1 before treatment to 1.6 at 1 month and to 1.4/10 at 6 months, demonstrating a long-term effect. 20 Similarly, a double-center retrospective analysis of percutaneous FICS demonstrated 87.1% rate of pain improvement in a series of cancer patients that included 25 pelvic locations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The technique is predominantly applied in the pelvic flat bones or femoral neck, although recent studies have suggested a potential role in other locations. 20,24 Applications for both prophylactic treatment and fixation of fractures have been evaluated.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…PS with pins, screws, or a combination of these materials to reinforce bone weakened by metastases has been described only in small retrospective and prospective series in the IR literature. 13,26,27 These options are typically utilized in locations that experience torsional forces, for example, the femoral neck and the humerus. In these early studies, PS has demonstrated reduced fracture rates, reduced pain, and improved function.…”
Section: Mechanical Reinforcementmentioning
confidence: 99%